The entrapment of trap design: Materiality, political economy and the shifting worlds of fixed gear fishing equipment - Swanson, Heather Anne (Journal of material culture, 2019)
Anthropologists have often focused on what one can read about the worlds of hunters and prey from the forms of traps. This article demonstrates, however, that a trap's design is not always tightly coupled to the worlds within which it is deployed. Using the case of Columbia River salmon traps, it shows how the social, economic and ecological roles of traps can dramatically change - even as their physical shape remains the same. In the late 19th century, these traps were lucrative for their owners, but unpopular with the region's gillnet fishermen. The fishermen feared that traps entrapped the community in a problematic form of political economy - that they created the wrong kind of subjects and social order, concentrating wealth in the hands of a small, lazy owner class. The fishermen argued that such problems inhered in the materiality of the traps and that their physical design produced inequality that jeapordized the community. The gillnetters ultimately won over the government with their arguments, and fish traps were banned. But the banning of traps has subsequently proved entrapping. Today, some of the river's salmon are listed as endangered species. Gillnets, which often kill fish before they are hauled in, do not allow fishermen to sort out endangered and unendangered fish; they are thus being phased out. Traps that keep fish alive in their holds would allow for sorting out and releasing endangered fish, and they are now heralded as an environmentally sustainable technology by conservationists. But after decades of arguments that traps embody and create unjust economic forms, it is logistically and socially difficult to bring back traps. Based on this example, this article proposes an approach to traps that gives special attention to how the material force of traps shifts as they are linked to different ecological contexts and practices of political economy.